Nobiletin Alleviates Non-alcoholic Steatohepatitis in MCD-Induced Mice by Regulating Macrophage Polarization - Wang, Si-wei; Lan, Tian; Sheng, Hao; Zheng, Fang; Lei, Mei-kang; Wang, Li-xia; Chen, Hang-fei; Xu, Chun-yi; Zhang, Feng (Frontiers in Physiology, 2021)
Nonalcoholic steatohepatitis (NASH) is an inflammatory disorder that is characterized by chronic activation of the hepatic inflammatory response and subsequent liver damage. The regulation of macrophage polarization in liver is closely related to the progression of NASH. The orphan nuclear receptor retinoic-acid-related orphan receptor α (RORα) and Krüppel-like factor 4 (KLF4) are key regulators which promote hepatic macrophages towards M2 phenotype and protect against NASH in mice. Nobiletin (NOB), a natural polymethoxylated flavone, is previously reported as a RORα regulator in diet-induced obese mice. However, it is still unclear whether NOB has the protective effect on NASH. In this study, we investigated the role of NOB in NASH using a methionine and choline deficient (MCD)-induced NASH mouse model. Our results showed that NOB ameliorated hepatic damage and fibrosis in MCD fed mice. NOB treatment reduced the infiltration of macrophages and neutrophils in the liver in MCD-fed mice. Of importance, NOB significantly increased the proportion of M2 macrophages and the expression of anti-inflammatory factors in vivo and in vitro. Meanwhile, NOB also decreased the population of M1 macrophages and the expression of proinflammatory cytokines. Mechanistically, NOB elevated KLF4 expression in macrophages. Inhibition of KLF4 abolished NOB regulated macrophage polarization. Furthermore, the regulation of NOB in KLF4 expression was dependent on RORα.